2017
DOI: 10.1021/acsphotonics.6b00755
|View full text |Cite
|
Sign up to set email alerts
|

Excitation Energy Dependent Ultrafast Luminescence Behavior of CdS Nanostructures

Abstract: Selected semiconductor nanostructures provide extremely localized coherent light sources. Here an ensemble of CdS nanostructures was excited by UV/vis femtosecond laser pulses and their ultrafast luminescence characteristics were investigated as functions of the pulse energy fluence and the photon quantum energy. All optical Kerr gating enabled studies of the emission dynamics with a time resolution of 150 fs avoiding any influence on the CdS emission. The initially observed emission built up after a delay of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Generally, the initial population of photoexcited carriers depends on both the pump fluence and the pump photon energy. 58 Here, we focus on the pumpfluence (carrier density) dependence of the lasing onset time by fixing the pump photon energy (E pump ). After excitation, the nonequilibrium hot carriers relaxes through a variety of interaction processes, for example, carrier−phonon interaction.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, the initial population of photoexcited carriers depends on both the pump fluence and the pump photon energy. 58 Here, we focus on the pumpfluence (carrier density) dependence of the lasing onset time by fixing the pump photon energy (E pump ). After excitation, the nonequilibrium hot carriers relaxes through a variety of interaction processes, for example, carrier−phonon interaction.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Such onset time delay strongly depends on the pump level, that is, the onset time of the laser emission decreases with elevated carrier density and eventually saturates at a lower minimum. 31 On the other hand, Karras et al 58 reported that the saturation minimum of the laser onset time was strongly affected by the excess photon energy E exc , denoted by E exc = E pump − E g , due to the different energetic pathway that the carriers have to thermalize through for different E exc . Consequently, it is considered to be a very effective way to tune the laser onset time of CsPbCl 3 microlasers by directly modulating the pump fluence as well as the pump photon quantum energy.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure d displays the typical lasing spectra as a function of the pulse energy density for this nanobelt cavity. A slight red shift of the optical mode occurs with increasing power because of the recombination of the electron–hole plasma. ,, The pulse energy density dependence of the laser output intensity is plotted on a double logarithmic scale in Figure e (blue points), which reveals a lasing threshold of ∼53 μJ/cm 2 . Emission transitions from spontaneous emission (43.5 μJ/cm 2 ) through amplified spontaneous emission (51.2 μJ/cm 2 ) to the entire lasing action (55.4 μJ/cm 2 ) are provided with increasing pulse energy density.…”
Section: Resultsmentioning
confidence: 99%
“…CdS, as one of the significant II–VI group semiconductors with a direct band gap of 2.42 eV at 300 K, has attracted increasing attention owing to its appealing applications in photocatalysts, [ 1–3 ] optoelectronics, [ 4 ] and photonics [ 5–7 ] based on their nonlinear properties. [ 8 ] Nanostructure construction is a commonly used approach to further modulate its physical or chemical behavior.…”
Section: Introductionmentioning
confidence: 99%